What is the value of entrepreneurial orientation on the network and performance? An examination in trade fairs context - Silva, Pedro (2021)
Purpose – The purpose of this paper is to examine the influence of entrepreneurial orientation on the network and exhibitor’s performance. The entrepreneurial orientation is seen as a highly competitive factor for the company, which can foster its trade fair business. Design/methodology/approach – A survey-based quantitative approach was adopted, including a questionnaire (n 5 362) applied to companies participating in trade fairs. To arrive at results, the study developed structural equations modeling techniques, using SPSS 24 and AMOS 20 software. Findings – The study demonstrates positive impacts of entrepreneurial orientation on network capability and consequent exhibitor’s non-sales performance and exhibitor’s sales performance. A conceptual model is presented. Research limitations/implications – The study was carried out mainly on Portuguese companies, restricting its generalization. In addition, the exhibitor’s performance was measured based on the exhibitors’ level of satisfaction and not on real sales results. Practical implications – The study offers a process which the results highlight such as innovativeness, proactivity, risk-taking, competitiveness and autonomy (dimensions of entrepreneurial orientation) as a mix of important ingredients for the exhibitor’s networking. The networking promotes intangible results (non-sales performance) that can generate sales (sales performance). Originality/value – The study is the first research to apply entrepreneurial orientation in the trade fair context and it also presents a relationship between non-sales performance and sales performance.